Pseudosarcomatous myofibroblastic proliferation of the appendix with an abdominal abscess due to diverticulum perforation: a case report - Tanaka, Tetsuya (Surg Case Rep, 2020)
BACKGROUND: Pseudosarcomatous myofibroblastic proliferation is a rare proliferative lesion of the submucosal stroma characterized by myofibroblast proliferation and inflammatory cell infiltration, and is mainly reported in the urinary system. CASE PRESENTATION: We report a 65-year-old male who was referred to our emergency room with right-side iliac fossa pain. The pain gradually worsened for approximately 2 months, and rebound tenderness was positive. Blood examination showed severe inflammatory findings, and enhanced computed tomography revealed a heterogeneous contrast-enhancing mass lesion measured to be 55 × 50 mm in size at the lower right abdomen. Based on these results, the patient was diagnosed with appendicitis with an abdominal abscess. As the inflammation was severe, we drained the abscess before performing surgery. Approximately 1 month after the abscess diminished, interval appendectomy was performed. Macroscopic findings of the resected specimen showed a perforated diverticulum of the appendix and a small adjacent nodule measured to be 14 mm in size. Histopathological examination with hematoxylin and eosin staining revealed that the nodule consisted of fibroblast proliferation and inflammatory cell infiltration. Furthermore, immunohistochemical examination showed positive for smooth muscle actin and desmin and negative for S-100, c-kit, and anaplastic lymphoma kinase. Based on these histopathological results, we diagnosed the nodule as an unusual case of a pseudosarcomatous myofibroblastic proliferation associated with perforation of the diverticulum of the appendix. CONCLUSION: Herein, we report a rare case of a pseudosarcomatous myofibroblastic proliferation that occurred in the appendix with diverticulitis.